The Books of Chronicles and Ezra-Nehemiah as a Project of New Future for Israel - Chrostowski, Waldemar (Collectanea Theologica, 2021)
1–2 Chronicles and Ezra-Nehemiah express a different approach to the future of Israel to that provided in the Earlier Prophets. Firstly, the nature and the dating of this part of the Hebrew Bible are discussed, suggesting the end of the fifth and the very beginning of the fourth century B.C. as the time of its origins. Secondly, the retrospect of the past in 1–2 Chronicles is presented with a very specific attitude towards the Exile. The article focuses on the detailed analysis of Ezra 4:1–5, a passage representing the very core of this book. Against the backdrop of the identity of the deputation visiting Jerusalem as seen by the author of Ezra and the completely different self-presentation of the envoys from the north, the serious conflict that ensues is described. It bears analogies with the former antagonisms and tensions between the kingdom of Judah and the kingdom of Israel. On the basis of this conflict, a new reality emerges, namely Judaism. The religion of the preexilic Israel was profoundly transformed, having been exclusively limited to those Judeans who had come back from the Exile. As a result of this separation, the question of the “true Israel” became more crucial, setting new direction for the project of the national and religious identity of biblical Israel.